Multi-location testing of a global collection of elite chickpea genotypes to identify stable sources of resistance to Ascochyta blight - Istanbuli, Tawffiq; Can, Canan; Talapov, T.; Kharrat, Mohamed; Bouhadida, Mariem; Omri, Noura; Fikre, A.; Zewdie, Asrat; Singh, Sarvjeet; Rani, Upasana; Tawkaz, Sawsan; Kemal, Seid Ahmed; et al. (Australian National Chickpea Ascochyta Blight, 2022)
Ascochyta blight (AB) of chickpea (Cicer arietinum L.) caused by Ascochyta rabiei (Pass.) Lab. is the most devastating disease that limits the productivity and production of chickpea in the world. The lack of high levels of stable sources of resistance makes chickpea production a risky business. The search for durable resistance genotypes and differentials to monitor shifts in pathogen populations are becoming a pressing research agenda. There is a need to understand the evolution of pathogen virulence and the number of resistant genes available in chickpea germplasm. Therefore, this research aimed to evaluate the global Ascochyta blight reference set in chickpea (GABRSC), which is expected to carry some of the resistant genes to AB has been identified in many countries. The GABRSC set (200 diverse genotypes) was evaluated in six geographic locations where AB is a major disease. The testing sites were Kafarshakhna (Lebanon), Merchouch (Morocco), Alem Tena (Ethiopia), Punjab University (India), Beja (Tunisia), and Gaziantep University (Turkey). The genotypes were planted following Alpha Lattice design in two replications in the 2021–22 cropping season. Disease severity was rated using a 1–9 rating scale. The REML analysis showed significant differences among genotypes (G), environments (E), and G x E interactions showing the possibility of different pathogen populations in different locations. The GGE biplot analyses showed that all environments were positively related. A total of 11 genotypes (S160454, SE26IN, S0110227, M 2635, S0110075, S160353, S0110028, 0110088, S0110195, S0110211, and S160483) were consistent in their resistance across sites with an average rating of ≤ 4. On the other hand, genotypes showed crossover interactions across locations. For example, PBA HatTrick was resistant in Ethiopia (but susceptible in Lebanon and FLIP84-48C was resistant in India but susceptible in Lebanon. This study will help us to understand the relationship between the host and pathogen and to design new AB differential sets. However, the resistant genotypes across locations identified in the present study would be useful in breeding programs.